2013
DOI: 10.1089/end.2013.0182
|View full text |Cite
|
Sign up to set email alerts
|

LaparoEndoscopic Single Site Orchidopexy for Intra-Abdominal Testes in the Pediatric Population with a Multichannel Single Port and Flexible Tip Laparoscope

Abstract: Our initial experience with this technique was favorable with excellent outcomes. LESS orchidopexy is facilitated with a MCSP and FTL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…All parents were extremely satisfied with the cosmetic results. Other studies have also shown similar results [ 9 , 10 ]. Wang et al illustrated that a transumbilical single-site multiport procedure resulted in a smaller scar and less pain [ 13 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All parents were extremely satisfied with the cosmetic results. Other studies have also shown similar results [ 9 , 10 ]. Wang et al illustrated that a transumbilical single-site multiport procedure resulted in a smaller scar and less pain [ 13 ].…”
Section: Discussionsupporting
confidence: 84%
“…In 2011, single-site LO was introduced in the pediatric population, offering the advantage of a concealed incision, which was well-received by parents [ 7 ]. However, existing reports are limited and primarily focus on non-palpable testes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean operative time for LESS orchidopexy in this report was longer than in the series reported by Noh et al [ 10 ], probably because of the use of the flexible tip laparoscope, but it was shorter than the time reported by Raju et al [ 8 ], who reported a technique using standard trocars through a single umbilical incision with an intraabdominal time of 126 minutes. The time reported by de Lima et al [ 9 ] was almost the same as in our first 3 patients.…”
Section: Discussioncontrasting
confidence: 62%
“…To our knowledge, this technique has been previously used for orchidopexy in a pediatric population by only four authors. Sultan et al [ 7 ] used an R-port in a 2-year-old boy; Raju et al [ 8 ] and de Lima et al [ 9 ] used rigid instruments in an 18-month-old child and for 3 boys, respectively; and Noh et al [ 10 ] reported a series of 17 patients in which a multichannel single port and flexible tip laparoscope were used. All of these studies showed LESS orchidopexy in children to be feasible, safe, and scarless, with no intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of procedures have been described for surgical management of IAT include laparoscopic single or staged orchidopexy [11], using multiple or single ports [12], or microvascular [13] procedures. The majority of IAT in the UK are managed with two-stage Fowler-Stephens laparoscopic orchidopexy (FSLO) whereby the testicular vessels are divided.…”
Section: Discussionmentioning
confidence: 99%